2003
DOI: 10.1109/lpt.2002.807928
|View full text |Cite
|
Sign up to set email alerts
|

Four-wave mixing based 10-Gb/s tunable wavelength conversion using a holey fiber with a high SBS threshold

Abstract: Abstract-We demonstrate a four-wave-mixing based wavelength converter using a 15-m highly nonlinear holey fiber (HF) with a high stimulated Brillouin scattering (SBS) threshold. Error-free efficient wavelength conversion of 10-Gb/s nonreturn-to-zero signal over a 10-nm bandwidth is reliably achieved. Our 15-m HF has a nonlinearity coefficient 70( 10) W 1 km 1 and an SBS threshold of more than 130 mW. The high SBS threshold is achieved by applying structural variation to the HF along its length during the fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The novel dispersion properties and high nonlinear coefficient obtainable can be used in numerous other ways, where the standard nonlinear fiber and the dispersionshifted fibers (DSF) have been used before. Applications count Raman Amplification [69,70] optical parametric amplifiers [71,72], soliton generation, guiding and compression [73][74][75] and Wavelength Conversion [2,76,77]. The high nonlinear coefficient obtainable reduces the need for long fiber lengths with for some applications greatly improved performance.…”
Section: Telecommunication Applicationsmentioning
confidence: 99%
“…The novel dispersion properties and high nonlinear coefficient obtainable can be used in numerous other ways, where the standard nonlinear fiber and the dispersionshifted fibers (DSF) have been used before. Applications count Raman Amplification [69,70] optical parametric amplifiers [71,72], soliton generation, guiding and compression [73][74][75] and Wavelength Conversion [2,76,77]. The high nonlinear coefficient obtainable reduces the need for long fiber lengths with for some applications greatly improved performance.…”
Section: Telecommunication Applicationsmentioning
confidence: 99%
“…Since the effective index of the holey cladding depends on the air hole arrangement and the wavelength, PCFs bring unique properties not seen in conventional optical fibers. [1][2][3][4] Hence, PCFs have been applied as functional fibers, for example, for dispersion control, 5,6) supercontinuum generation, [7][8][9] wavelength conversion, [9][10][11] and so on. Since low-loss PCFs were developed, 12,13) PCFs have been expected as transmission lines in fiber optic communication systems.…”
Section: Introductionmentioning
confidence: 99%
“…In using a light source with no output fiber, the light from the light source is launched into the PCF through its facet, where an objective lens is used so that the diameter of the Gaussian beam from the light source matches the MFD of the PCF. 1,8,10,11) Index matching fluid is sometimes used to strip off light in cladding modes. 1) It was reported that >50% of coupling efficiency was obtained using an objective lens.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the wavelength conversion mechanisms of the converters constructed from microstructure fibers are due to cross-phase modulation and four-wave mixing [10][11]. The self-phase modulation (SPM) effects is usually used for pulse shaping in all-optical switch [12].…”
Section: Introductionmentioning
confidence: 99%